TextGrid, TEXTvre, and DARIAH: Sustainability of Infrastructures for Textual Scholarship - Mark Hedges; Heike Neuroth; Kathleen M. Smith; Tobias Blanke; Laurent Romary; Marc Küster; Malcolm Illingworth (Journal of the Text Encoding Initiative, 2013)
A variety of initiatives for developing virtual research environments, research infrastructures, and cyberinfrastructures have been funded in recent years. The systems produced vary considerably, but they all face the issue of sustainability, namely how to ensure the continued existence of a resource once the project that created it has finished. This paper addresses the sustainability issues faced by the TextGrid and TEXTvre virtual research environments for textual scholarship, examining the inter-project collaboration and cross-fertilization that took place, and investigating how the projects benefited from this exchange. It also examines how their sustainability is being facilitated by the more general-purpose DARIAH infrastructure, and conversely how their existing collaboration can serve as a model for future collaborations within the DARIAH community.